COMPREHENSIVE ENVIRONMENTAL EVALUATION OF BUKIT ASAM POWER PLANT COAL ASH - ALI R. KURNIAWAN; NIA R. HADIJAH (Puslitbang tekMIRA, 2012)
Indonesian government regulation No 85 year 1999 regarding management of hazardous material states that in order to identify and to define coal ash as hazardous material or non hazardous material, the coal ash should be evaluated by characteristic and toxicity tests. In this study, the properties of coal ash sample from Bukit Asam power plant were evaluated using chemical analyses and bioassay of Lethal Concentration (LC50-96 hour) and Lethal Dose (LD50-96 hour). The chemical analyses shows that the main chemical compositions of Bukit Asam coal ash were SiO2 (60.6 %) and Al2O3 (22.8%). Bukit Asam coal ash was categorized as non toxic criteria as its LC50-96 hour value exceeded 100,000 ppm. Meanwhile, the result of LD50-96 hour shows that mortality of mice was not found in every dose given (500; 5,000; 15,000; 30,000; 50,000 mg/kg BW) for 0-96 hours of observation so it can be classified as a non hazardous material based on the Indonesian government regula- tion. The results of TCLP test reveal that the concentrations of all the heavy metals were invariably well below the permissible limits for discharge of effluents according to Indonesia regulation and US. EPA standard. Thus, it was also categorized as non hazardous material. Radiation dose of Bukit Asam coal ash was 0.41 mSv/year and it was under standard limits for human being (1 mSv/year). The mean heavy metal contents in Brassica chinensis tissues with three times cultivation were above the WHO limits level. However, the addition of 17.5% coal ash in growth media drastically decreased heavy metals content (Cu: 25.6; Pb: 66.6; Cd: 48.8 dan Cr: 8.29%) into the lowest content. The results generated from this study indicated that Bukit Asam coal ash has a vast potential for reclamation of degraded coal mining land.